From Desert to Medicine: A Review of Camel Genomics and Therapeutic Products - Ali, Amanat; Baby, Bincy; Vijayan, Ranjit (Frontiers in Genetics, 2019)
Camels have an important role in the lives of human beings, especially in arid regions, due to their multipurpose role and unique ability to adapt to harsh conditions. In spite of its enormous economic, cultural, and biological importance, the camel genome has not been widely studied. The size of camel genome is roughly 2.38 GB, containing over 20,000 genes. The unusual genetic makeup of the camel is the main reason behind its ability to survive under extreme environmental conditions. The camel genome harbours several unique variations which are being investigated for the treatment of several disorders. Various natural products from camels have also been tested and prescribed as adjunct therapy to control the progression of ailments. Interestingly, the camel employs unique immunological and molecular mechanisms against pathogenic agents and pathological conditions. Here, we broadly review camel classification, distribution and breed as well as recent progress in the determination of the camel genome, its size, genetic distribution, response to various physiological conditions, immunogenetics and the medicinal potential of camel gene products.